Portal Vein Recanalization Transjugular Intrahepatic Portosystemic Shunt for Noncirrhotic Chronic Portal Vein Thrombosis Leading to Successful Pregnancy: Case Report - Andy Yu; Gabriel M. Knight; Justin Boike; Bartley Thornburg; Riad Salem (Gastro Hep Advances)
Portal vein recanalization transjugular intrahepatic portosystemic shunt (PVR-TIPS) is a safe and effective procedure for decompression of portal hypertension (PH). In this short case series, 2 women with chronic noncirrhotic portal vein thrombosis were treated with PVR-TIPS. Both patients hoped to conceive. Without treatment for their PH, their pregnancies posed a significant risk of life-threatening variceal bleeding. Both patients tolerated the procedure well and delivered without complications of PH. In future cases of noncirrhotic portal vein thrombosis in patients hoping to conceive, PVR-TIPS should be considered for definitive treatment of PH.